A case series of cholesteatoma spread in middle ear cleft - Mohanty, Deeganty; Santhaiah, Kakumanu; Soujanya, Robba Rama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: This study aimed to describe the spread of cholesteatoma in middle ear cleft. Methods: The 20 patients diagnosed with chronic otitis media, squamosal type (cholesteatoma) who underwent mastoidectomy exploration were included in this study. The main emphasis was to find out the extent and spread of cholesteatoma into the middle ear cleft. Results: The result of the study showed 50% of cases spread to middle ear cavity (20% -meso tympanum, 15%-sinus tympani,15%-facial recess), 20% into the attic, 30% into adits, antrum and mastoid air cell system. Conclusions: All of our patients underwent mastoid exploratory surgery. In half of the cases, the cholesteatoma was restricted to middle ear cavity, while in remaining 50% it has extended to attic, aditus mastoid antrum and mastoid air cells. Disease clearance was effective with no post-operative complication or recurrence in first 50% cases. Other 50% of cases required extensive surgery for disease clearance.